FANATISME SUPORTER SEPAKBOLA DITINJAU DARI ASPEK SOSIO-ANTROPOLOGIS (STUDI KASUS AREMANIA MALANG) - Assyaumin, Moch. Ian Brilian; Yunus, Mahmud; Raharjo, Slamet (Jurnal Sport Science, 2017)
Abstract :The purpose of this research is to find out (1) fanaticisms of Aremania soccer fans from the socio-anthropological aspect, and (2) the factors that influence the fanatic behavior of Aremanias supporters in supporting Arema team. This research uses qualitative descriptive approach, data collection technique through observation, interview, and documentation. The results of research: 1) Aremania is one of the fanatic and loyal fans, 2) Aremania always establish good relations with the surrounding environment. The conclusion of the research results indicate that Aremania is a very fanatic supporter in supporting Arema.Keywords :fanaticism, supporters, football